Serum ferritin and iron deficiency in adolescent schoolchildren with depression in northern Sudan: unmatched case-control study - Hassan, Ahmed A.; Alharbi, Hatim Y.; Adam, Ishag (Frontiers in Psychiatry, 2025)
BackgroundThe direction of the association between depression and serum ferritin among adolescents needs to be explored further. There is no data on the association between serum ferritin and depression in Sudan. Therefore, the current study aimed to compare serum ferritin and iron deficiency between adolescents with depression and healthy controls in northern Sudan.MethodsAn unmatched case-control study was conducted among adolescent school children in River Nile State, Sudan. The cases were adolescents with depression (n = 61), and an equal number of healthy adolescents were controls. The Patient Health Questionnaire (PHQ−9) was used to assess depression. Multivariate regression analysis was performed.ResultsThe median serum ferritin level (6.3 [IQR 2.9–13.8] μg/l vs. 25.4 [IQR 19.5–37.1] μg/l, p <0.001) was significantly lower in adolescents with depression than in healthy controls. A significant negative correlation was found between the depression scale and serum ferritin levels (r = -0.596, p < 0.001). In multivariate analysis, while increasing age (adjusted odds ratio [AOR] = 1.44, 95% confidence interval [CI] 1.05–1.98), being female (AOR = 11.19, 95% CI 4.17–29.99), and iron deficiency (AOR = 76.87, 95% CI 9.08–650.0) were positively associated with depression, serum ferritin was negatively associated with depression (AOR = 0.96, 95% CI 0.94–0.99).ConclusionThis study revealed a notable negative association between serum ferritin levels and depression. Adolescents with depression should be assessed for serum ferritin and iron deficiency.